An oxidation-resistant sintering copper paste under air atmosphere and a preparation method thereof

CN123022288APending Publication Date: 2026-10-30NANJING UNIV OF AERONAUTICS & ASTRONAUTICS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611189655.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-06
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]然而,铜的化学活性较高,铜颗粒表面极易与空气中的氧气发生反应生成氧化层,这一问题成为制约烧结铜产业化应用的核心技术瓶颈

Benefits of technology

[0024](1)本发明提供的空气烧结抗氧化铜膏及其制备方法,抗氧化烧结适应性强:通过将还原剂与聚乙二醇粘结剂复配,不同链长的粘结剂对还原剂的溶解度不同,且不同链长的粘结剂在加热过程中的分解速度也不同。利用这一现象,以粘结剂作为还原剂的缓释载体,利用粘结剂链长对还原剂释放过程进行调控,使还原剂释放动力学与铜粉氧化动力学相匹配,有效解决低温阶段还原剂过早耗尽的问题,从而使铜膏能够在空气气氛下完成抗氧化烧结。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123022288A_ABST
    Figure CN123022288A_ABST
Patent Text Reader

Abstract

The application discloses a kind of to realize air atmosphere under oxidation resistance sintering copper paste and preparation method thereof, belong to electronic packaging material preparation field, applicable to SiC power chip sintering interconnection.The copper paste is with submicron copper particle of 0.1 μm to 0.9 μm particle size as metal base material, and contains the organic carrier formed by polyethylene glycol binder and at least one reducing agent of glucose, citric acid, ascorbic acid.Reducing agent is ground pretreatment when preparing, to make binder and reducing agent mix with mass ratio 10:3 to 10:1, the organic carrier obtained and submicron copper powder are mixed by 2000r / min centrifugation 5min to be made into sintering copper paste and sealed cold storage.The copper paste can be used for SiC power chip sintering interconnection under air atmosphere, reduce the dependence on vacuum, inert atmosphere protection process, improve the adverse effects of copper particle oxidation under air sintering condition on interconnection performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electronic packaging material preparation, and in particular to a sintered copper paste for electronic packaging and its preparation method. Background Technology

[0002] Silicon carbide (SiC), as a core material for third-generation wide-bandgap semiconductors, has become a core substrate for high-end power electronics in fields such as new energy vehicles, smart grids, and aerospace due to its excellent properties, including high breakdown field strength, high thermal conductivity, high electron saturation drift velocity, and high temperature resistance. The operating junction temperature of SiC power chips is significantly higher than that of traditional silicon-based chips. Conventional packaging interconnect materials can no longer meet the application requirements of high temperature and high reliability. Upgrading the interconnect system has become a key step in the industrialization of SiC devices. SiC power packaging interconnect materials have undergone multiple generations of technological iteration. Early widely used tin-based solders, due to their low thermal conductivity and poor compatibility with SiC chips and ceramic substrates, were prone to thermal stress cracking and interface delamination under high-temperature cycling conditions. Furthermore, their melting point and upper limit of thermal stability could not meet the long-term operating requirements of SiC devices above 200℃, leading to their gradual replacement by high-performance sintered interconnect materials.

[0003] Sintered silver, with its ultra-high thermal and electrical conductivity, has become the mainstream interconnect material for high-performance SiC packaging, effectively solving the core pain point of high-temperature interconnects. However, the high cost of silver powder raw materials and its problems such as electromigration and easy agglomeration during sintering significantly increase the manufacturing cost of SiC devices, limiting its large-scale promotion in the civilian field. Against this backdrop, sintered copper, with its comprehensive advantages of low raw material cost, thermal / electrical conductivity close to that of sintered silver, and thermal expansion coefficient highly compatible with the SiC packaging system, has become the optimal alternative that balances performance and cost. It is the core development direction for achieving low-cost, high-reliability sintered interconnects for SiC power chips and has attracted much attention from the industry.

[0004] However, copper is highly chemically reactive, and the surface of copper particles readily reacts with oxygen in the air to form an oxide layer. This problem has become a core technological bottleneck restricting the industrial application of sintered copper. During the sintering process, the copper powder oxide layer continues to thicken as the temperature rises. This not only hinders the diffusion and bonding between copper particles and inhibits the formation of sintering necks, significantly deteriorating the electrical and thermal conductivity and mechanical strength of the sintered body, but also leads to an increase in interfacial contact resistance, affecting the long-term operational stability of SiC devices. Existing anti-oxidation solutions for sintered copper mainly fall into two categories. One category involves using vacuum or inert gas protection during sintering, which effectively prevents oxidation but requires high-end specialized equipment, significantly increasing production equipment and process costs and reducing production efficiency. The other category involves adding excessive amounts of organic reducing agents to the copper paste in an attempt to eliminate the oxide layer through reduction reactions. However, traditional reducing agents suffer from a mismatch between decomposition kinetics and copper powder oxidation kinetics. At low temperatures, the reducing agent is prone to rapid decomposition and premature depletion, while at high temperatures, the copper powder oxide layer grows excessively without sufficient reducing agent for reduction. Even with increased reducing agent addition, it is difficult to achieve effective anti-oxidation across the entire temperature range. Furthermore, the residual reducing agent can lead to increased porosity in the sintered body, further affecting interconnect performance.

[0005] In summary, existing technologies struggle to achieve efficient and high-quality oxidation-resistant sintering of copper in an air atmosphere. Developing a copper paste material and preparation method that meets the requirements of SiC packaging and enables oxidation-resistant sintering in an air atmosphere has become a key technological challenge that urgently needs to be overcome in the field of SiC power semiconductor packaging interconnects. This invention was developed under this technological background. Summary of the Invention

[0006] The purpose of this patent is to achieve the slow-release effect of the reducing agent during sintering by designing a suitable reducing agent and binder system and controlling the dissolution and release of the reducing agent in the binder, thereby achieving antioxidant copper sintering in an air atmosphere.

[0007] To solve the above-mentioned technical problems, the present invention adopts the following technical solution:

[0008] An anti-oxidation sintering copper paste for use in an air atmosphere comprises, by weight percentage, 80% to 90% submicron copper particles and 10% to 20% organic carrier, wherein the organic carrier is composed of a binder and a reducing agent, wherein the mass ratio of the binder to the reducing agent is 10:3 to 10:1, and the submicron copper particles are copper particles that have formed a surface copper oxide layer through air storage.

[0009] Furthermore, the reducing agent is one, a combination of two, or a combination of three of the following: analytical grade glucose C6H12O6, analytical grade citric acid C6H8O7, and analytical grade ascorbic acid C6H8O6.

[0010] Furthermore, the adhesive is one, a combination of two, or a combination of three of polyethylene glycol 200, polyethylene glycol 300, and polyethylene glycol 400.

[0011] Furthermore, the submicron copper particles have a particle size of 0.1 μm to 0.9 μm.

[0012] A method for preparing an anti-oxidation sintering copper paste in an air atmosphere, used for the anti-oxidation sintering copper paste in an air atmosphere as described in any one of claims 1 to 5, characterized in that it includes the following steps:

[0013] Step S1: Store the submicron copper powder in air to form a copper oxide layer on the surface of the submicron copper powder;

[0014] Step S2: Grind the reducing agent for pretreatment;

[0015] Step S3: Mix the binder and the pre-treated reducing agent with a mass ratio of 10:3 to 10:1 to obtain an organic carrier;

[0016] Step S4: Mix the submicron copper powder and the organic carrier in a high-speed centrifuge to obtain sintered copper paste, wherein the organic carrier accounts for 10% to 20% of the total mass of the sintered copper paste;

[0017] Step S5: Seal and refrigerate the sintered copper paste.

[0018] Step S6: The SiC power chip is sintered and interconnected using the sintering copper paste in an air atmosphere.

[0019] Furthermore, in step S2, the reducing agent is one, a combination of two, or a combination of three of the following: analytical grade ascorbic acid C6H8O6, analytical grade glucose C6H12O6, and analytical grade citric acid C6H8O7.

[0020] Furthermore, in step S2, the grinding pretreatment involves grinding the reducing agent in an agate mortar for 10 minutes.

[0021] Furthermore, in step S4, the high-speed centrifuge operates at a speed of 2000 r / min and a mixing time of 5 min.

[0022] Furthermore, in step S6, the sintering temperature of the sintered interconnect is 250°C, the sintering pressure is 20 MPa, and the sintering time is 5 min.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) The air-sintering antioxidant copper paste and its preparation method provided by the present invention have strong adaptability to antioxidant sintering: by compounding the reducing agent with polyethylene glycol binder, the solubility of the reducing agent in binders with different chain lengths is different, and the decomposition rate of binders with different chain lengths is also different during the heating process. Taking advantage of this phenomenon, the binder is used as a slow-release carrier of the reducing agent, and the release process of the reducing agent is controlled by the chain length of the binder, so that the release kinetics of the reducing agent is matched with the oxidation kinetics of copper powder, effectively solving the problem of premature depletion of the reducing agent in the low-temperature stage, thereby enabling the copper paste to complete antioxidant sintering in an air atmosphere.

[0025] (2) The air-sintering antioxidant copper paste and its preparation method provided by the present invention have good sintering quality stability: a copper oxide layer is formed on the surface of submicron copper particles during air storage. This oxide layer is called a pre-oxidation layer. Under the action of a subsequent reducing agent, the pre-oxidation layer is reduced in situ to ultrafine nano copper particles, which is beneficial to control the surface state of copper particles. At the same time, the ultrafine nanostructure formed on the surface of submicron copper particles can increase the surface activity of particles, shorten the atomic diffusion path, promote the formation of sintering necks, and improve the sintering bonding effect between copper particles in air atmosphere.

[0026] (3) The air-sintering anti-oxidation copper paste and its preparation method provided by the present invention have low packaging application costs and good process compatibility: the copper paste can be used for SiC power chip sintering interconnection in an air atmosphere, reducing the dependence on vacuum sintering equipment, inert atmosphere protection equipment and excessive reducing agent addition. On the basis of ensuring the electrical conductivity, thermal conductivity and mechanical properties of the sintered copper layer, it is beneficial to reduce the packaging interconnection cost of SiC power devices and improve the convenience of engineering applications. Attached Figure Description

[0027] Figure 1 This invention relates to the microstructure of a copper sintering layer under air atmosphere, which is achieved by an anti-oxidation sintering copper paste under air atmosphere and its preparation method.

[0028] Figure 2 Energy dispersive X-ray spectroscopy (EDS) surface scan of the microstructure of copper sintered layers under air atmosphere;

[0029] Figure 3 The elemental energy spectrum of the energy dispersive X-ray spectroscopy (EDS) surface scan of the microstructure of the copper sintered layer under air atmosphere. Detailed Implementation

[0030] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0031] An anti-oxidation sintering copper paste for use in an air atmosphere comprises, by weight percentage, 80% to 90% submicron copper particles and 10% to 20% organic carrier, wherein the organic carrier is composed of a binder and a reducing agent, wherein the mass ratio of the binder to the reducing agent is 10:3 to 10:1, and the submicron copper particles are copper particles that have formed a surface copper oxide layer through air storage.

[0032] Furthermore, the reducing agent is one, a combination of two, or a combination of three of the following: analytical grade glucose C6H12O6, analytical grade citric acid C6H8O7, and analytical grade ascorbic acid C6H8O6.

[0033] Furthermore, the adhesive is one, a combination of two, or a combination of three of polyethylene glycol 200, polyethylene glycol 300, and polyethylene glycol 400.

[0034] Furthermore, the submicron copper particles have a particle size of 0.1 μm to 0.9 μm.

[0035] A method for preparing an anti-oxidation sintering copper paste in an air atmosphere, used for the anti-oxidation sintering copper paste in an air atmosphere as described in any one of claims 1 to 5, characterized in that it includes the following steps:

[0036] Step S1: Store the submicron copper powder in air to form a copper oxide layer on the surface of the submicron copper powder;

[0037] Step S2: Grind the reducing agent for pretreatment;

[0038] Step S3: Mix the binder and the pre-treated reducing agent with a mass ratio of 10:3 to 10:1 to obtain an organic carrier;

[0039] Step S4: Mix the submicron copper powder and the organic carrier in a high-speed centrifuge to obtain sintered copper paste, wherein the organic carrier accounts for 10% to 20% of the total mass of the sintered copper paste;

[0040] Step S5: Seal and refrigerate the sintered copper paste.

[0041] Step S6: The SiC power chip is sintered and interconnected using the sintering copper paste in an air atmosphere.

[0042] Furthermore, in step S2, the reducing agent is one, a combination of two, or a combination of three of the following: analytical grade ascorbic acid C6H8O6, analytical grade glucose C6H12O6, and analytical grade citric acid C6H8O7.

[0043] Furthermore, in step S2, the grinding pretreatment involves grinding the reducing agent in an agate mortar for 10 minutes.

[0044] Furthermore, in step S4, the high-speed centrifuge operates at a speed of 2000 r / min and a mixing time of 5 min.

[0045] Furthermore, in step S6, the sintering temperature of the sintered interconnect is 250°C, the sintering pressure is 20 MPa, and the sintering time is 5 min.

[0046] Example 1:

[0047] Step S1: Copper powder pretreatment: Submicron copper powder is stored in air until use.

[0048] Step S2, Pretreatment of reducing agent: Glucose (C6H12O6) of analytical grade is slowly ground in an agate mortar for 10 min to avoid its high-temperature decomposition.

[0049] Step S3: Mix the binder polyethylene glycol 200 with the reducing agent glucose C6H12O6 ground in step S2 at a ratio of 10:3 to obtain an organic carrier.

[0050] Step S4: Mix the submicron copper powder with the organic carrier obtained in step S3 in a centrifuge at a speed of 2000 r / min for 5 min. The organic carrier accounts for 15 Wt. of the total mass of the sintered copper paste.

[0051] Step S5: Seal and refrigerate the prepared sintered copper paste.

[0052] Step S6: Using the sintering copper paste, the SiC power chip is sintered with oxidation resistance under air atmosphere. The sintering process is 250 °C, 20 MPa, 5 min.

[0053] Example 2:

[0054] Step S1: Copper powder pretreatment: Submicron copper powder is stored in air until use.

[0055] Step S2, Pretreatment of reducing agent: Ascorbic acid (C6H8O6) of analytical grade is slowly ground in an agate mortar for 10 min to avoid its high-temperature decomposition.

[0056] Step S3: Mix the binder polyethylene glycol 300 with the reducing agent ascorbic acid C6H8O6 ground in step S2 at a ratio of 10:1 to obtain an organic carrier.

[0057] Step S4: Mix the submicron copper powder with the organic carrier obtained in step S3 in a centrifuge at a speed of 2000 r / min for 5 min. The organic carrier accounts for 20 Wt. of the total mass of the sintered copper paste.

[0058] Step S5: Seal and refrigerate the prepared sintered copper paste.

[0059] Step S6: Using the sintering copper paste, the SiC power chip is sintered with oxidation resistance under air atmosphere. The sintering process is 250 °C, 20 MPa, 5 min.

[0060] Example 3:

[0061] Step S1: Copper powder pretreatment: Submicron copper powder is stored in air until use.

[0062] Step S2, Pretreatment of reducing agent: Analytical grade citric acid (C6H8O7) is slowly ground in an agate mortar for 10 min to avoid its high-temperature decomposition.

[0063] Step S3: Mix the binder polyethylene glycol 400 with the reducing agent citric acid C6H8O7 ground in step S2 at a ratio of 10:1 to obtain an organic carrier.

[0064] Step S4: Mix the submicron copper powder with the organic carrier obtained in step S3 in a centrifuge at a speed of 2000 r / min for 5 min. The organic carrier accounts for 15 Wt. of the total mass of the sintered copper paste.

[0065] Step S5: Seal and refrigerate the prepared sintered copper paste.

[0066] Step S6: Using the sintering copper paste, the SiC power chip is sintered with oxidation resistance under air atmosphere. The sintering process is 250 °C, 20 MPa, for 5 min.

[0067] In other embodiments, the binder may be polyethylene glycol 200, polyethylene glycol 300, or polyethylene glycol 400, and the reducing agent may be glucose, ascorbic acid, or citric acid, thereby forming nine combinations of single binder and single reducing agent, and each combination can be used to prepare sintered copper paste according to steps S1 to S6.

[0068] To verify the antioxidant sintering effect of the copper paste of the present invention in air atmosphere, the microstructure and elemental analysis of the sintered copper layer were performed.

[0069] like Figure 1 The figure shows the microstructure of the copper sintered layer under air atmosphere. As can be seen from the figure, the sintered copper solder paste exhibits good sinterability, presents a uniform porous structure, and no copper oxide layer is observed (the contrast between the two is different).

[0070] like Figure 2 As shown, for Figure 1 Energy-dispersive X-ray spectroscopy (EDS) surface scans were used for qualitative and quantitative analysis of the elemental composition of micro-regions in the material. The image shows that the main element in the sintered copper layer is Cu, with small amounts of carbon and oxygen. These carbon and oxygen elements mainly originate from the decomposition and residues of organic matter.

[0071] like Figure 3 As shown, Figure 2 The elemental energy spectrum of EDS was obtained. The main element was Cu, with trace amounts of carbon and oxygen observed.

[0072] Table 1 shows the elemental quantitative analysis of the energy dispersive X-ray spectroscopy (EDS) surface scan of the microstructure of the copper sintered layer under air atmosphere. As can be seen from the table, the oxygen content is 0.77 wt%, which is at an extremely low level, indicating that oxidation-resistant sintering under air atmosphere was achieved.

[0073] Table 1 Elemental Quantitative Analysis Table

[0074]

[0075] In summary, this invention, through the combination of submicron copper particles, a reducing agent, and a polyethylene glycol binder, enables sintered copper paste to be used for SiC power chip sintering interconnection in an air atmosphere, and through... Figures 1 to 3 The microstructure and elemental analysis results verified its antioxidant sintering effect under air atmosphere.

[0076] This specification uses specific examples to illustrate the principles and implementation methods of the present invention. The descriptions of the above embodiments are only for the purpose of helping to understand the method and core ideas of the present invention. Furthermore, those skilled in the art will recognize that, based on the ideas of the present invention, there will be changes in the specific implementation methods and application scope. Therefore, the content of this specification should not be construed as a limitation of the present invention.

Claims

1. A copper paste for achieving oxidation-resistant sintering in an air atmosphere, characterized in that, The composition comprises 80% to 90% submicron copper particles and 10% to 20% organic carrier by weight percentage. The organic carrier consists of a binder and a reducing agent, wherein the mass ratio of the binder to the reducing agent is 10:3 to 10:

1. The submicron copper particles are copper particles that have formed a surface copper oxide layer through air storage.

2. The copper paste for achieving oxidation-resistant sintering in air atmosphere according to claim 1, characterized in that, The reducing agent is one, two, or three of the following: analytical grade glucose (C6H12O6), analytical grade citric acid (C6H8O7), and analytical grade ascorbic acid (C6H8O6).

3. The copper paste for achieving oxidation-resistant sintering in air atmosphere according to claim 1, characterized in that, The adhesive is one, a combination of two, or a combination of three of polyethylene glycol 200, polyethylene glycol 300, and polyethylene glycol 400.

4. The copper paste for achieving oxidation-resistant sintering in air atmosphere according to claim 1, characterized in that, The submicron copper particles have a particle size of 0.1 μm to 0.9 μm.

5. A method for preparing an anti-oxidation sintering copper paste in an air atmosphere, used for preparing an anti-oxidation sintering copper paste in an air atmosphere as described in any one of claims 1 to 4, characterized in that, Includes the following steps: Step S1: Store the submicron copper powder in air to form a copper oxide layer on the surface of the submicron copper powder; Step S2: Grind the reducing agent for pretreatment; Step S3: Mix the binder and the pre-treated reducing agent with a mass ratio of 10:3 to 10:1 to obtain an organic carrier; Step S4: Mix the submicron copper powder and the organic carrier in a high-speed centrifuge to obtain sintered copper paste, wherein the organic carrier accounts for 10% to 20% of the total mass of the sintered copper paste; Step S5: Seal and refrigerate the sintered copper paste. Step S6: The SiC power chip is sintered and interconnected using the sintering copper paste in an air atmosphere.

6. The method for preparing antioxidant sintering copper paste in air atmosphere according to claim 5, characterized in that, In step S2, the reducing agent is one, a combination of two, or a combination of three of the following: analytical grade ascorbic acid C6H8O6, analytical grade glucose C6H12O6, and analytical grade citric acid C6H8O7.

7. The method for preparing antioxidant sintering copper paste in air atmosphere according to claim 5, characterized in that, In step S2, the grinding pretreatment involves grinding the reducing agent in an agate mortar for 10 minutes.

8. The method for preparing antioxidant sintering copper paste under air atmosphere according to claim 5, characterized in that, In step S4, the high-speed centrifuge rotates at 2000 r / min and the mixing time is 5 min.

9. The method for preparing antioxidant sintering copper paste in air atmosphere according to claim 5, characterized in that, In step S6, the sintering temperature of the sintered interconnect is 250°C, the sintering pressure is 20 MPa, and the sintering time is 5 min.